A mixing dispersant for positive electrode slurry, and a preparation method and application thereof

CN115895682BActive Publication Date: 2026-11-03EVE POWER CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211449003.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-18
Publication Date
2026-11-03
Estimated Expiration
2042-11-18

AI Technical Summary

Technical Problem

Existing dispersants are prone to oxidation under high temperature and high pressure conditions, which leads to a decrease in the interfacial contact performance of lithium-ion batteries, affecting the first charge and discharge efficiency and cycle performance, and posing a risk of thermal runaway.

Method used

A mixed dispersant of styrene-acrylate copolymer and hydrogenated nitrile is used, taking advantage of its functional monomers and highly saturated structure that are stable under high pressure to improve heat resistance and high pressure resistance, reduce viscosity changes, and enhance slurry stability and cell wetting performance.

Benefits of technology

It improves the initial charge-discharge efficiency, cycle performance, and safety performance of lithium-ion batteries, reduces the phenomenon of excessively rapid cell temperature rise and uneven heat distribution, reduces the risk of decomposition, and ensures the stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115895682B_ABST
    Figure CN115895682B_ABST
Patent Text Reader

Abstract

The application provides a mixed dispersant for a positive electrode slurry, a preparation method and application thereof. The mixed dispersant comprises a combination of a first dispersant and a second dispersant; the first dispersant comprises at least one of a styrene-acrylate copolymer, polypropylpyrrolidone, polyacrylamide, N-vinylpyrrolidone copolymer or butadiene-acrylonitrile copolymer; and the second dispersant comprises hydrogenated butyronitrile. The mixed dispersant provided by the application improves the high-temperature stability of the slurry, reduces the risk of slurry blocking of the lithium supplement system, thereby solving the problem of too fast temperature rise of the battery cell caused by the multi-platform in the lithium supplement system, reducing the uneven heat distribution in the battery cell, and reducing the risk of easy oxidation and decomposition and loss of activity of the conventional dispersant under high pressure conditions, ensuring that the first charge-discharge efficiency, cycle performance and safety performance of the battery are not affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of dispersant materials technology, specifically relating to a mixed dispersant for positive electrode slurry, its preparation method, and its application. Background Technology

[0002] With the rapid development of technology, the market demand for high-power lithium batteries is increasing. The particle size distribution of cathode materials is a key factor affecting charge and discharge performance. An ideal particle size distribution optimizes the energy capacity and power output of lithium batteries. Small-particle cathode materials can increase the specific surface area of ​​active materials and reduce the diffusion path of lithium ions in the battery, thereby improving the electrochemical reactivity of lithium-ion batteries. However, if the particle size of the cathode material is too small, it is prone to agglomeration, which can lead to problems such as lower compaction density, resulting in lower battery energy density; and poorer homogenization effect, leading to excessively high viscosity or low solid content in the slurry. Currently, existing technologies mainly use the addition of dispersants to the cathode slurry to solve the problem of agglomeration and clogging.

[0003] Dispersants are adsorbed onto the surface of cathode materials through physical or chemical action, preventing particle collision and agglomeration. This results in a slurry with low viscosity and high solids content, effectively solving the particle agglomeration problem and reducing solvent usage, thereby lowering production costs. Common types of dispersants include polypropylene pyrrolidone (PVP) or polyacrylamide (PAM).

[0004] To reduce irreversible capacity loss, researchers have addressed the issue by adding lithium replenishing agents to the slurry. In lithium replenishment systems, the cell often needs to be charged to a high voltage of 4.2V–4.5V during the formation stage to ensure the replenishing agent can completely extract lithium ions and realize its specific capacity. However, lithium replenishment systems exhibit two or more voltage plateaus, and the lithium-ion insertion / extraction process generates significant heat. Compared to conventional lithium iron phosphate systems, the battery temperature rise can vary from 5°C to 30°C, significantly increasing the risk of thermal runaway and explosion.

[0005] In addition, the dispersants disclosed in the prior art are prone to oxidation and side reactions under high temperature and high pressure conditions in the lithium replenishment system, which affects the battery's interfacial contact performance, initial charge and discharge capacity and cycle performance. In severe cases, it may even lead to thermal runaway of lithium-ion batteries or even explosion.

[0006] Therefore, based on the above problems, it is necessary to develop a high-temperature and high-pressure resistant dispersant that can not only give the slurry good flowability and processability, but also reduce the risk of thermal runaway of the battery. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a mixed dispersant for positive electrode slurries, its preparation method, and its application. This invention provides a mixed dispersant resistant to high temperatures and high pressures, thereby improving the stability of the slurry and the safety performance of the battery.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a mixed dispersant for positive electrode slurry, the mixed dispersant comprising a combination of a first dispersant and a second dispersant;

[0010] The first dispersant includes at least one of styrene-acrylate copolymer, polyacrylamide, N-vinylpyrrolidone copolymer, or butadiene-acrylonitrile copolymer;

[0011] The second dispersant includes hydrogenated butyronitrile.

[0012] This invention utilizes a combination of a first dispersant and a second dispersant to prepare a mixed dispersant. The first dispersant possesses high-pressure performance primarily because it contains functional monomers, such as those containing carboxyl, hydroxyl, epoxy, and amino groups. These functional groups ensure structural stability under high pressure. The second dispersant, hydrogenated butyronitrile, exhibits a highly saturated structure, thus enhancing its heat resistance and high-pressure resistance. Furthermore, the mixed dispersant provided by this invention not only exhibits minimal viscosity change at high temperatures, significantly improving slurry stability and reducing the risk of slurry blockage in lithium-ion systems, but also effectively enhances the wetting performance of the battery cell and reduces its internal resistance. This addresses the issue of excessively rapid temperature rise in the battery cell due to multiple plateaus in lithium-ion systems, reduces uneven heat distribution within the cell, and mitigates the risk of conventional dispersants easily oxidizing, decomposing, and losing activity under high pressure. This ensures that the battery's initial charge-discharge efficiency, cycle performance, and safety performance remain unaffected.

[0013] Preferably, the molecular weight of the first dispersant is 6000 to 15000, for example, it can be 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000, 10500, 11000, 11500, 12000, 12500, 13000, 13500, 14000, 14500, or 15000. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0014] In this invention, the molecular weight of the first dispersant is adjusted to a suitable value. If the molecular weight is too low, the dispersion efficiency decreases, the specific surface area and volume of the positive electrode active material increase, and thus the viscosity increases rapidly. Conversely, the larger the molecular weight, the slower the dissolution rate. In addition, a large molecular weight dispersant will generate greater steric hindrance, resulting in excessively low viscosity of the slurry and increasing the difficulty of coating.

[0015] Preferably, the molecular weight of the second dispersant is 50,000 to 100,000, for example, 50,000, 60,000, 70,000, 80,000, 90,000, or 100,000. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0016] In this invention, the molecular weight of the second dispersant is adjusted to a suitable value. If the molecular weight is too low, the dispersion efficiency and heat resistance will be poor; otherwise, the structure will be unstable and the solubility will be low.

[0017] Preferably, the mass ratio of the first dispersant and the second dispersant in the mixed dispersant is (20-40):(60-80), for example, it can be 20:80, 25:75, 30:70, or 40:60. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0018] In this invention, by adjusting the mass ratio of the first dispersant and the second dispersant, the second dispersant with a higher mass ratio is used because hydrogenated nitrile butadiene can act as both a positive electrode binder and a dispersant, playing an important role in the electrical performance of the battery cell. If the mass ratio is too low, the battery will not be able to withstand high-temperature conditions, leading to separator ablation, obstruction of lithium-ion transport paths, and increased lithium plating. Conversely, if the mass ratio is too high, the battery will not be able to withstand high-voltage conditions, the electrolyte will easily decompose, and the gas production during battery formation and subsequent testing will increase.

[0019] In a second aspect, the present invention provides a method for preparing a mixed dispersant for positive electrode slurry according to the first aspect, the method comprising the following steps:

[0020] The first dispersant powder and the second dispersant powder are mixed to obtain the mixed dispersant for the positive electrode slurry.

[0021] It should be noted that the present invention uses solid-phase mixing of the first dispersant powder and the second dispersant powder without adding solvent.

[0022] In this invention, the temperature for solid-phase mixing of the first dispersant powder and the second dispersant powder is 25-45°C, and the humidity is controlled at 0-10%.

[0023] Preferably, the first dispersant powder comprises at least one of styrene-acrylate copolymer, polypropylene pyrrolidone, polyacrylamide, N-vinylpyrrolidone copolymer, or butadiene-acrylonitrile copolymer.

[0024] Preferably, the preparation method of the styrene-acrylate copolymer includes the following steps: mixing styrene, acrylate and deionized water, heating and then adding an initiator and deionized water to carry out emulsion polymerization to obtain the styrene-acrylate copolymer.

[0025] Preferably, the molar ratio of styrene to acrylate is (1:9):(9:1), for example, it can be 1:9, 2:8, 3:7, 4:6, 5:5, 6:4. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0026] Preferably, the heating temperature is 45-55°C, for example, 45°C, 50°C, 52°C, or 55°C; the heating rate is 200-600 rpm, for example, 200 rpm, 400 rpm, 500 rpm, or 600 rpm; and the heating time is 20-120 min, for example, 20 min, 40 min, 60 min, 80 min, 100 min, or 120 min.

[0027] Preferably, the initiator comprises potassium persulfate or sodium persulfate.

[0028] Preferably, the emulsion polymerization time is 100-200 min, for example, 100 min, 120 min, 140 min, 160 min, 180 min, or 200 min.

[0029] Preferably, the second dispersant comprises hydrogenated butyronitrile.

[0030] Preferably, the preparation method of the second dispersant powder includes the following steps: mixing nitrile rubber latex and catalyst, then adding initiator and defoamer, and reacting to obtain the second dispersant powder.

[0031] Preferably, the catalyst comprises any one or a combination of at least two of palladium, calcium, rhodium or ruthenium.

[0032] Preferably, the mixing temperature is 45-50°C, for example, 45°C, 47°C, 49°C, or 50°C.

[0033] Preferably, the initiator comprises any one or a combination of at least two of oxygen, hydrogen peroxide, or hydrazine hydrate.

[0034] Preferably, the defoamer comprises any one or a combination of at least two of the following: alcohol compounds, fatty acid compounds, fatty acid ester compounds, amide compounds, phosphate ester compounds, organosilicon compounds, polyether compounds, or polyether-modified polysiloxane compounds.

[0035] In this invention, the alcohol compounds include any one or a combination of at least two of diethylhexanol, isooctanol, isoamyl alcohol, or diisobutylmethanol. These defoamers are linear molecules with strong hydrophobicity and weak hydrophilicity, which can effectively increase the intermolecular diffusion rate and reduce the viscosity of the slurry.

[0036] In this invention, the fatty acid ester compounds include diol distearate or diethylene glycol laurate. This type of defoamer has advantages such as readily available raw materials, high environmental performance, and low production cost.

[0037] Thirdly, the present invention provides a positive electrode slurry, the positive electrode slurry comprising a positive electrode active material, a conductive agent, a binder, a dispersant, and a lithium supplementer, wherein the dispersant is a mixed dispersant for positive electrode slurry according to the first aspect.

[0038] Preferably, the mass percentage of positive electrode active material in the positive electrode slurry is 90% to 95%, for example, it can be 90%, 91%, 92%, 93%, 94%, or 95%. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0039] Preferably, the mass percentage of the conductive agent in the positive electrode slurry is 3% to 4%, for example, 3%, 3.2%, 3.5%, 3.8%, or 4%. For the sake of brevity, the values ​​within the above range will not be listed one by one.

[0040] Preferably, the mass percentage of binder in the positive electrode slurry is 1% to 2%, for example, it can be 1%, 1.2%, 1.5%, 1.8%, or 2%. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0041] Preferably, the mass percentage of dispersant in the positive electrode slurry is 0.1% to 0.2%, for example, it can be 0.1%, 0.12%, 0.15%, 0.18%, or 0.2%. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0042] In this invention, common lithium battery dispersants, such as polypropylene pyrrolidone (PVP) and polyacrylamide (PAM), require the addition of approximately 0.4% to 0.8% of the dispersant and a reduction in the solid content of the cathode slurry to control the viscosity of the cathode slurry within the ideal range. However, the mixed dispersant provided by this invention only requires the addition of 0.1% to 0.2% to achieve its effect. On the one hand, it can increase the solid content of the cathode slurry by approximately 5% to 8%, reduce the amount of N-methylpyrrolidone used, and lower production costs. On the other hand, the reduced mass of the dispersant can be distributed to the lithium replenishing agent according to the proportion of active material, thereby effectively improving the capacity and electrical performance of the battery cell.

[0043] Preferably, the mass percentage of lithium supplementation agent in the positive electrode slurry is 0.2% to 0.5%, for example, it can be 0.2%, 0.3%, 0.4%, or 0.5%. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0044] In this invention, the lithium replenishing agent includes, but is not limited to, any one or a combination of at least two of Li2NiO2, Li5FeO4, Li3N, Li2O2, Li2S, LiF, or Li2O.

[0045] Preferably, the viscosity of the positive electrode slurry is 8000 mPa·s to 15000 mPa·s, for example, it can be 8000 mPa·s, 9000 mPa·s, 10000 mPa·s, 11000 mPa·s, 12000 mPa·s, 13000 mPa·s, 14000 mPa·s, or 15000 mPa·s. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0046] In this invention, the viscosity of the positive electrode slurry is adjusted to be within a suitable range. If the viscosity is too low, the surface density of the coated electrode will be uneven, resulting in increased internal polarization and reduced capacity of the battery. Conversely, if the viscosity is too high, coating will not be possible, no electrode will be produced, and slurry will be wasted.

[0047] Preferably, the solid content of the positive electrode slurry is 50% to 70%, for example, it can be 50%, 55%, 60%, 65%, or 70%. For the sake of brevity, the values ​​in the above range will not be listed one by one.

[0048] Fourthly, the present invention provides a positive electrode sheet, which is prepared from the positive electrode slurry according to the third aspect.

[0049] Fifthly, the present invention provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the positive electrode comprises the positive electrode according to the fourth aspect.

[0050] The lithium-ion battery prepared from the positive electrode provided by this invention has high initial charge-discharge efficiency, stable cycle performance, and safety performance.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] This invention provides a mixed dispersant prepared by combining a first dispersant and a second dispersant. Utilizing the principle that the unique formation structures of the two dispersants determine their formation characteristics, the mixed dispersant exhibits improved heat resistance and high-pressure resistance. Furthermore, the mixed dispersant provided by this invention not only shows minimal viscosity change at high temperatures, significantly improving slurry stability and reducing the risk of slurry blockage in lithium-ion replenishment systems, but also effectively enhances the wetting performance of the battery cell and reduces its internal resistance. This addresses the problem of excessively rapid temperature rise in the battery cell due to multiple plateaus in lithium-ion replenishment systems, reduces uneven heat distribution within the cell, and mitigates the risk of conventional dispersants easily oxidizing, decomposing, and losing activity under high-pressure conditions. This ensures that the battery's initial charge-discharge efficiency, cycle performance, and safety performance remain unaffected. Attached Figure Description

[0053] Figure 1 A comparison graph showing the viscosity changes of the positive electrode slurry provided in Example 1 and Comparative Example 3. Detailed Implementation

[0054] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0055] Example 1

[0056] This embodiment provides a mixed dispersant for positive electrode slurry, comprising a combination of a styrene-acrylate copolymer with a molecular weight of 10,000 and a hydrogenated butyronitrile with a molecular weight of 70,000. The mass ratio of the styrene-acrylate copolymer to the hydrogenated butyronitrile in the mixed dispersant is 30:70.

[0057] This embodiment provides a method for preparing the above-mentioned mixed dispersant, which includes the following steps:

[0058] Styrene, acrylate, and deionized water were mixed at room temperature, with a molar ratio of styrene to acrylate of 5:5. The mixture was heated at 50°C and stirred at a stirring rate of 400 rpm for 70 min. Potassium persulfate initiator and deionized water were added to carry out emulsion polymerization. At the same time, nitrogen gas was continuously introduced into the reaction system. After reacting for 150 min, styrene-acrylate copolymer powder was obtained.

[0059] Nitrile rubber latex and palladium catalyst were mixed at 48°C, and then hydrazine hydrate initiator and diethylhexanol defoamer were added. The mixture was stirred at a constant temperature for 1 hour to obtain hydrogenated nitrile rubber powder.

[0060] Styrene-acrylate copolymer powder and hydrogenated nitrile butadiene powder were mixed in a solid phase at a mixing temperature of 35°C and a humidity of 5% to obtain a mixed dispersant for positive electrode slurry.

[0061] This embodiment also provides a positive electrode sheet and its preparation method, which includes the following steps:

[0062] A positive electrode slurry was prepared by mixing 95% lithium iron phosphate, 3% conductive carbon black, 1.5% polyvinylidene fluoride, 0.15% mixed dispersant and 0.35% Li2NiO2 lithium supplementer by mass percentage, and adding N-methylpyrrolidone solvent. The viscosity of the positive electrode slurry was 12000 mPa·s and the solid content was 60%. The slurry was then uniformly coated on aluminum foil, dried, cold pressed and die-cut into positive electrode sheets.

[0063] Figure 1 This indicates that the viscosity of the slurry prepared by the mixed dispersant provided by the present invention has a small variation range, the stability of the slurry is significantly improved, and the risk of cathode slurry clogging is reduced.

[0064] Example 2

[0065] This embodiment provides a mixed dispersant for positive electrode slurry, comprising a combination of a styrene-acrylate copolymer with a molecular weight of 8000 and a hydrogenated butyronitrile with a molecular weight of 60000. The mass ratio of the styrene-acrylate copolymer to the hydrogenated butyronitrile in the mixed dispersant is 25:75.

[0066] This embodiment provides a method for preparing the above-mentioned mixed dispersant, which includes the following steps:

[0067] Styrene, acrylate, and deionized water were mixed at room temperature, with a molar ratio of styrene to acrylate of 3:7. The mixture was heated at 50°C and stirred at a stirring rate of 400 rpm for 70 min. Potassium persulfate initiator and deionized water were added to carry out emulsion polymerization. At the same time, nitrogen gas was continuously introduced into the reaction system. After reacting for 150 min, styrene-acrylate copolymer powder was obtained.

[0068] Nitrile rubber latex and palladium catalyst were mixed at 48°C, and then hydrazine hydrate initiator and diethylhexanol defoamer were added. The mixture was stirred at a constant temperature for 1 hour to obtain hydrogenated nitrile rubber powder.

[0069] Styrene-acrylate copolymer powder and hydrogenated nitrile butadiene powder were mixed in a solid phase at a mixing temperature of 35°C and a humidity of 5% to obtain a mixed dispersant for positive electrode slurry.

[0070] This embodiment also provides a positive electrode sheet and its preparation method, which includes the following steps:

[0071] A positive electrode slurry was prepared by mixing 95% lithium iron phosphate, 3% conductive carbon black, 1.5% polyvinylidene fluoride, 0.15% mixed dispersant and 0.35% Li2NiO2 lithium supplementer by mass percentage, and adding N-methylpyrrolidone solvent. The viscosity of the positive electrode slurry was 10000 mPa·s and the solid content was 55%. The slurry was then uniformly coated on aluminum foil, dried, cold pressed and die-cut into positive electrode sheets.

[0072] Example 3

[0073] This embodiment provides a mixed dispersant for positive electrode slurry, comprising a combination of a styrene-acrylate copolymer with a molecular weight of 12,000 and a hydrogenated butyronitrile with a molecular weight of 80,000. The mass ratio of the styrene-acrylate copolymer to the hydrogenated butyronitrile in the mixed dispersant is 35:65.

[0074] This embodiment provides a method for preparing the above-mentioned mixed dispersant, which includes the following steps:

[0075] Styrene, acrylate, and deionized water were mixed at room temperature, with a molar ratio of styrene to acrylate of 7:3. The mixture was heated at 50°C and stirred at a stirring rate of 400 rpm for 70 min. Potassium persulfate initiator and deionized water were added to carry out emulsion polymerization. At the same time, nitrogen gas was continuously introduced into the reaction system. After reacting for 150 min, styrene-acrylate copolymer powder was obtained.

[0076] Nitrile rubber latex and palladium catalyst were mixed at 48°C, and then hydrazine hydrate initiator and diethylhexanol defoamer were added. The mixture was stirred at a constant temperature for 1 hour to obtain hydrogenated nitrile rubber powder.

[0077] Styrene-acrylate copolymer powder and hydrogenated nitrile butadiene powder were mixed in a solid phase at a mixing temperature of 35°C and a humidity of 5% to obtain a mixed dispersant for positive electrode slurry.

[0078] This embodiment also provides a positive electrode sheet and its preparation method, which includes the following steps:

[0079] A positive electrode slurry was prepared by mixing 95% lithium iron phosphate, 3% conductive carbon black, 1.5% polyvinylidene fluoride, 0.15% mixed dispersant, and 0.35% Li2NiO2 lithium supplementer by mass percentage, and adding N-methylpyrrolidone solvent. The viscosity of the positive electrode slurry was 13000 mPa·s, and the solid content was 65%. The slurry was then uniformly coated on aluminum foil, dried, cold-pressed, and die-cut into positive electrode sheets.

[0080] Example 4

[0081] This embodiment provides a mixed dispersant for positive electrode slurry, comprising a combination of polyacrylonitrile (K-30) with a molecular weight of 6000 and hydrogenated nitrile butyronitrile with a molecular weight of 50000. The mass ratio of polyacrylonitrile to hydrogenated nitrile butyronitrile in the mixed dispersant is 20:80.

[0082] This embodiment provides a method for preparing the above-mentioned mixed dispersant, which includes the following steps:

[0083] Nitrile rubber latex and ruthenium catalyst were mixed at 45°C, and then hydrogen peroxide initiator and glycol distearate defoamer were added. The mixture was stirred at a constant temperature for 1 hour to obtain hydrogenated nitrile rubber powder.

[0084] Polypropylene pyrrolidone powder and hydrogenated nitrile butadiene powder were mixed in a solid phase at a mixing temperature of 35°C and a humidity of 5% to obtain a mixed dispersant for positive electrode slurry.

[0085] This embodiment also provides a positive electrode sheet and its preparation method, which includes the following steps:

[0086] A positive electrode slurry was prepared by mixing 94% lithium iron phosphate, 4% conductive carbon black, 1.5% polyvinylidene fluoride, 0.1% mixed dispersant and 0.4% Li2NiO2 lithium supplementer by mass percentage, and adding N-methylpyrrolidone solvent. The viscosity of the positive electrode slurry was 8000 mPa·s and the solid content was 50%. The slurry was then uniformly coated on aluminum foil, dried, cold pressed and die-cut into positive electrode sheets.

[0087] Example 5

[0088] This embodiment provides a mixed dispersant for positive electrode slurry, comprising a combination of polyacrylonitrile (K-30) with a molecular weight of 15,000 and hydrogenated butyronitrile with a molecular weight of 100,000. The mass ratio of polyacrylonitrile to hydrogenated butyronitrile in the mixed dispersant is 40:60.

[0089] This embodiment provides a method for preparing the above-mentioned mixed dispersant, which includes the following steps:

[0090] Nitrile rubber latex and ruthenium catalyst were mixed at 50°C, and then hydrogen peroxide initiator and glycol distearate defoamer were added. The mixture was stirred at a constant temperature for 1 hour to obtain hydrogenated nitrile rubber powder.

[0091] Polypropylene pyrrolidone powder and hydrogenated nitrile butadiene powder were mixed in a solid phase at a mixing temperature of 35°C and a humidity of 5% to obtain a mixed dispersant for positive electrode slurry.

[0092] This embodiment also provides a positive electrode sheet and its preparation method, which includes the following steps:

[0093] A positive electrode slurry was prepared by mixing 94.3% lithium iron phosphate, 3.5% conductive carbon black, 1.5% polyvinylidene fluoride, 0.2% mixed dispersant and 0.5% Li2NiO2 lithium supplementer by mass percentage, and adding N-methylpyrrolidone solvent. The viscosity of the positive electrode slurry was 15000 mPa·s and the solid content was 70%. The slurry was then uniformly coated on aluminum foil, dried, cold pressed and die-cut into positive electrode sheets.

[0094] Example 6

[0095] The difference between this embodiment and Embodiment 1 is that the molecular weight of the styrene-acrylate copolymer is 5000, while all other aspects are the same as in Embodiment 1.

[0096] Example 7

[0097] The difference between this embodiment and Example 1 is that the molecular weight of the styrene-acrylate copolymer is 16,000, while all other aspects are the same as in Example 1.

[0098] Example 8

[0099] The difference between this embodiment and Example 1 is that the molecular weight of the hydrogenated butyronitrile is 40,000, while all other aspects are the same as in Example 1.

[0100] Example 9

[0101] The difference between this embodiment and Example 1 is that the molecular weight of the hydrogenated butyronitrile is 110,000, while all other aspects are the same as in Example 1.

[0102] Example 10

[0103] The difference between this embodiment and Example 1 is that the mass ratio of styrene-acrylate copolymer to hydrogenated butyronitrile in the mixed dispersant is 10:90, while all other aspects are the same as in Example 1.

[0104] Example 11

[0105] The difference between this embodiment and Example 1 is that the mass ratio of styrene-acrylate copolymer and hydrogenated butyronitrile in the mixed dispersant is 50:50, while all other aspects are the same as in Example 1.

[0106] Example 12

[0107] The difference between this embodiment and Embodiment 1 is that the viscosity of the positive electrode slurry is 7000 mPa·s, while all other aspects are the same as in Embodiment 1.

[0108] Example 13

[0109] The difference between this embodiment and Embodiment 1 is that the viscosity of the positive electrode slurry is 14000 mPa·s, while all other aspects are the same as in Embodiment 1.

[0110] Comparative Example 1

[0111] The difference between this comparative example and Example 1 is that the styrene-acrylate copolymer is replaced with an equal amount of hydrogenated nitrile butadiene, while all other aspects are the same as in Example 1.

[0112] Comparative Example 2

[0113] The difference between this comparative example and Example 1 is that hydrogenated butyronitrile is replaced with an equal amount of styrene-acrylate copolymer, while all other aspects are the same as in Example 1.

[0114] Comparative Example 3

[0115] The difference between this comparative example and Example 1 is that the mixed dispersant is replaced with an equal amount of conventional polypropylene pyrrolidone dispersant; otherwise, they are the same as in Example 1.

[0116] Application Examples 1 to 13 and Comparative Application Examples 1 to 3

[0117] Lithium-ion batteries were prepared using the positive electrode sheets provided in Examples 1 to 13 and Comparative Examples 1 to 3, and the preparation methods are as follows:

[0118] Preparation of the positive electrode: as described above;

[0119] Preparation of negative electrode sheet: The negative electrode active material graphite, conductive carbon black and sodium carboxymethyl cellulose were thoroughly stirred in a mass ratio of 95%:1.5%:3.5% and then deionized water was added to obtain negative electrode slurry. The prepared slurry was coated on copper foil, cold-pressed, baked and die-cut into strips to prepare negative electrode sheet.

[0120] Electrolyte preparation: 1 mol of LiPF6 was used as the lithium salt, and the solvent was a mixed solvent composed of EC / DC / EMC (volume ratio of 1:1:1).

[0121] Preparation of lithium-ion batteries: The positive electrode sheet, polypropylene separator and negative electrode sheet are wound into a core under certain pressure. The prepared core is placed in an aluminum shell. Under negative pressure, the electrolyte is injected into the cell. After it has been allowed to stand for a while, subsequent processes such as encapsulation, formation and capacity testing are carried out to obtain the lithium-ion battery.

[0122] Test conditions

[0123] The lithium-ion batteries prepared in Application Examples 1 to 13 and Comparative Application Examples 1 to 3 were subjected to performance tests, and the test methods are as follows:

[0124] (1) Internal resistance test: Connect the positive and negative wires of the internal resistance tester to the positive and negative terminals of the battery, and record the internal resistance displayed on the instrument.

[0125] (2) Calibration capacity test: Place the battery under the corresponding temperature conditions and charge and discharge it with a current of 0.5C to compare its discharge capacity.

[0126] (3) Cyclic performance test: The battery is placed under the corresponding temperature conditions and charged and discharged.

[0127] Charging: 0.5C current, constant current and constant voltage charging to 3.65V, cut-off current: 0.05C;

[0128] Discharge: 0.5C current, constant current discharge to 2.5V;

[0129] The cell charge-discharge cycle test was performed using the above steps, and the capacity retention rate after 500 cycles / 2000 cycles was compared. The calculation formula is as follows:

[0130] X-cycle capacity retention rate = (X-cycle capacity / first-cycle discharge capacity) × 100%, where X can be any number of cycles.

[0131] The test results are shown in Table 1:

[0132] Table 1

[0133]

[0134]

[0135] As can be seen from the data in Table 1, Examples 1-5 demonstrate that the present invention provides a mixed dispersant, which is prepared by combining a first dispersant and a second dispersant. Utilizing the principle that the unique chemical formation structures of the two dispersants determine their chemical formation characteristics, the heat resistance and high pressure resistance of the mixed dispersant are improved. Examples 6-7 show that if the molecular weight is too low, the dispersion efficiency decreases, and the specific surface area and volume of the positive electrode active material increase, thus causing a rapid increase in viscosity; conversely, the larger the molecular weight, the slower the dissolution rate. Examples 8-9 show that controlling the molecular weight of hydrogenated nitrile butadiene oxide (HNO₃) allows for the regulation of the dispersion efficiency and heat resistance of the dispersant. Examples 10-11 show that adjusting the mass ratio of styrene-acrylate copolymer and hydrogenated nitrile butadiene oxide (HNO₃) achieves a good dispersion effect. Examples 12-13 illustrate that adjusting the viscosity of the positive electrode slurry facilitates a good coating effect.

[0136] Comparative Examples 1 and 2 are single dispersants; Comparative Example 3 is a conventional dispersant, and their effects are not as good as the mixed dispersant provided in this application.

[0137] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A mixing and dispersing agent for positive electrode slurry, characterized in that, The mixed dispersant comprises a combination of a first dispersant and a second dispersant; The first dispersant is a styrene-acrylate copolymer; The second dispersant includes hydrogenated butyronitrile; The molecular weight of the first dispersant is 6000~15000; The molecular weight of the second dispersant is 50,000 to 100,000; The mass ratio of the first dispersant and the second dispersant in the mixed dispersant is (25~40):(60~75); The mixed dispersant is prepared by the following method, which includes the following steps: The first dispersant powder and the second dispersant powder are mixed in a solid phase to obtain the mixed dispersant for the positive electrode slurry; the solid phase mixing temperature is 25~45℃.

2. A method for preparing a mixed dispersant for positive electrode slurry according to claim 1, characterized in that, The method includes the following steps: The first dispersant powder and the second dispersant powder are mixed in a solid phase to obtain the mixed dispersant for the positive electrode slurry. The solid-phase mixing temperature is 25~45℃; the first dispersant powder is a styrene-acrylate copolymer, and the second dispersant powder includes hydrogenated nitrile butadiene.

3. The method according to claim 2, characterized in that, The preparation method of the styrene-acrylate copolymer includes the following steps: mixing styrene, acrylate and deionized water, heating and then adding an initiator and deionized water to carry out emulsion polymerization to obtain the styrene-acrylate copolymer.

4. The method according to claim 3, characterized in that, The molar ratio of styrene to acrylate is (1:9):(9:1).

5. The method according to claim 3, characterized in that, The heating temperature is 45~55℃, the rate is 200~600rpm, and the time is 20~120min.

6. The method according to claim 3, characterized in that, The initiator includes potassium persulfate or sodium persulfate.

7. The method according to claim 3, characterized in that, The emulsion polymerization time is 100~200 min.

8. The method according to claim 2, characterized in that, The preparation method of the second dispersant powder includes the following steps: mixing nitrile rubber latex and catalyst, then adding initiator and defoamer, and reacting to obtain the second dispersant powder.

9. The method according to claim 8, characterized in that, The catalyst comprises any one or a combination of at least two of palladium, calcium, rhodium, or ruthenium.

10. The method according to claim 8, characterized in that, The mixing temperature is 45–50°C.

11. The method according to claim 8, characterized in that, The initiator includes any one or a combination of at least two of oxygen, hydrogen peroxide, or hydrazine hydrate.

12. The method according to claim 8, characterized in that, The defoamer includes any one or a combination of at least two of the following: alcohol compounds, fatty acid compounds, fatty acid ester compounds, amide compounds, phosphate ester compounds, organosilicon compounds, polyether compounds, or polyether-modified polysiloxane compounds.

13. A positive electrode slurry, characterized in that, The positive electrode slurry includes a positive electrode active material, a conductive agent, a binder, a dispersant, and a lithium supplement agent. The dispersant is a mixed dispersant for positive electrode slurry according to claim 1. The viscosity of the positive electrode slurry is 8000 mPa·s to 15000 mPa·s.

14. The positive electrode slurry according to claim 13, characterized in that, The positive electrode slurry contains 90% to 95% by mass of the positive electrode active material.

15. The positive electrode slurry according to claim 13, characterized in that, The conductive agent in the positive electrode slurry has a mass percentage content of 3% to 4%.

16. The positive electrode slurry according to claim 13, characterized in that, The binder in the positive electrode slurry has a mass percentage content of 1% to 2%.

17. The positive electrode slurry according to claim 13, characterized in that, The mass percentage of dispersant in the positive electrode slurry is 0.1% to 0.2%.

18. The positive electrode slurry according to claim 13, characterized in that, The lithium supplement agent in the positive electrode slurry has a mass percentage content of 0.2% to 0.5%.

19. The positive electrode slurry according to claim 13, characterized in that, The solid content of the positive electrode slurry is 50%~70%.

20. A positive electrode plate, characterized in that, The positive electrode sheet is prepared from the positive electrode slurry according to any one of claims 13-19.

21. A lithium-ion battery, characterized in that, The lithium-ion battery includes a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the positive electrode includes the positive electrode according to claim 20.

Citation Information

Patent Citations

  • Slurry composition for electrochemical element electrodes, electrode for electrochemical elements, electrochemical element, and method for producing slurry composition for electrochemical element electrodes

    WO2019054173A1